(untitled) (Research, Society and Development, 2022)
The objective of this work is to carry out an integrative review on the effectiveness and importance of early diagnosis of cervical cancer, especially in menopausal women. This study is based on an integrative literature review in which it is based on literature already published by classic and current authors who have been able to contribute with all their knowledge over the years and synthesizes relevant information that is consistent with the topic addressed. The databases used to search for scientific articles were: Natural Library of Medicine (PUBMED), Scientific Electronic Library Online (SCIELO), Latin American and Caribbean Literature in Health Sciences (LILACS). Of the sample used n=16 (100%), n=3 articles were published in the year 2022 (19%), n=3 articles published in the year 2021 (19%), n=6 articles published in the year of 2020 (37%), n=3 articles published in the year 2019 (19%) and n=1 articles published in the year 2018 (6%). The Pap smear test is effective, but still has a lower sensitivity in detecting cancer, with the HPV-DNA test being a better and current option for screening the disease, and there may be more early diagnoses, thus reducing, in a significant number cases of cervical cancer, since for women, especially in the climacteric phase, menopause, the faster the diagnosis, the more chances and possibilities of cure.